Amide N–C Bond Activation: A Graphical Overview of Acyl and Decarbonylative Coupling - Liu, Chengwei; Szostak, Michal (SynOpen, 2023)
This Graphical Review provides an overview of amide bond activation achieved by selective oxidative addition of the N–C(O) acyl bond to transition metals and nucleophilic acyl addition, resulting in acyl and decarbonylative coupling, together with key mechanistic details pertaining to amide bond distortion underlying this reactivity manifold.
Keywords: C–N activation; amide bond activation; acyl coupling; decarbonylative coupling; acyl addition; catalysis